(untitled) (Physical Culture and Sport: Scientific Perspective, 2023)
The article examines the concept of the readiness of future teachers of physical culture to teach sports games in general secondary education institutions as the ability of students for successful physical culture and methodological activities, the ability to learn sports games, the methodology of their teaching for students of general secondary education institutions, to develop their own methods and to motivate young students to sports games and a healthy lifestyle. The components of the readiness of future physical culture teachers to teach sports games in general secondary education institutions are outlined: motivational, cognitive and activity. The technology of forming the readiness of future physical culture teachers to teach sports games in general secondary education institutions has been developed, which involves three stages: preparatory-motivational, methodical-technological and final-prolonged. The organizational and pedagogical conditions for the implementation of each stage of the author’s technology are defined. Thus, the preparatory and motivational stage involves the implementation of organizational and pedagogical conditions for motivating students to learn sports games, their teaching methods for students of secondary schools, the development of their own methods of teaching sports games and encouraging student youth to sports games and a healthy lifestyle; the methodical-technological stage accommodates the organizational and pedagogical conditions for studying sports games, methods of teaching them for students of ZZSO, development of own methods of teaching sports games and stimulating student youth to sports games and a healthy lifestyle; the final-prolonged stage determines the organizational and pedagogical conditions for the presentation by students of their own methods of teaching sports games and the stimulation of student youth to sports games and a healthy lifestyle, as well as orientation towards improving pedagogical skills and physical culture-methodical competence. The principles of implementation of the technology of formation of the readiness of future physical culture teachers to teach sports games in general secondary education institutions are singled out: sequence, continuity, interactivity, dynamic differentiation, multi-functionality, freedom of choice and cooperation.